Oxidative catalytic removal of hydrocarbons over Pt/Al2O3 catalysts - Garetto, Teresita Francisca (2000)
The reaction kinetics, structure sensitivity, and in situ activation of cyclopentane and methane combustions were studied on Pt/Al2O3 catalysts of different platinum and chlorine loadings. The catalyst activities were evaluated through both conversion vs. temperature (light-off curves) and conversion vs. time catalytic tests. Cyclopentane oxidation turnover rates (TOF) increased dramatically with increasing Pt crystallite size while TOF values for methane oxidation increased only three times by diminishing the Pt dispersion from 65 to 15%. The reaction orders in oxygen were one (cyclopentane) and zero (CH4). For both reactions, the orders and activation energies did not change by changing the Pt dispersion. Results are interpreted in basis of two different reaction mechanisms over the metallic Pt active sites. Cyclopentane oxidation proceeds via a surface redox mechanism, being the dissociative adsorption of oxygen the rate-determining step. The observed turnover rate increase with increasing Pt particle size reflects an increase in the density of reactive Pt–O species resulting from higher Pt oxidation rates. The methane oxidation mechanism is interpreted in terms of Mars–van Kravelen reduction–oxidation pathways which include the abstraction of the first hydrogen on the adsorbed methane molecule as the rate-determining step. Low-conversion catalytic tests performed at constant temperature showed that on well-dispersed Pt/Al2O3 catalysts the cyclopentane conversion increases with time on stream, while the methane activity decreases. Activating induction periods during the oxidation of cyclopentane are related to the sintering of the metallic phase in reaction conditions. Hot-spots on the metallic particles together with the presence of gaseous water cause the formation of larger, more reactive, Pt crystallites, even at mild reaction conditions. The activation phenomenon ab initio of the reaction is not verified for methane oxidation on Pt/Al2O3 catalysts. The different structure sensitivity of the slowest steps in the reaction–oxidation mechanisms explains the existence of induction periods on well-dispersed Pt catalysts only for cyclopentane oxidation.